Levetiracetam Pharmacokinetics in a Patient Receiving Continuous Venovenous Hemofiltration and Venoarterial Extracorporeal Membrane Oxygenation. Issue 8 (3rd August 2015) - Nei, Scott D.; Wittwer, Erica D.; Kashani, Kianoush B.; Frazee, Erin N.
<x xml:space="preserve">Abstract</x> Levetiracetam is a first‐line therapy for seizures in critically ill patients because of its clinical efficacy, minimal drug interactions, and wide therapeutic window. The primary mechanism of levetiracetam clearance is renal, and the drug has a low molecular weight. It is hydrophilic and exhibits minimal protein binding. Thus it is expected that levetiracetam will be removed by continuous venovenous hemofiltration (CVVH), with limited clearance by venoarterial extracorporeal membrane oxygenation (ECMO). We describe the case of a 67‐year‐old man who was admitted to the cardiovascular surgery intensive care unit after cardiac arrest and initiation of venoarterial ECMO. His course was complicated by multiorgan dysfunction including acute renal failure requiring CVVH. On hospital day 6, intravenous levetiracetam, at a loading dose of 2000 mg followed by a maintenance dose of 1000 mg every 12 hours, was initiated for new‐onset seizures. The volume of distribution was 0.65 L/kg, and clearance was measured with peak (ranging from 26.5–39.8 μg/ml) and trough (ranging from 13.9–18.2 μg/ml) concentrations. Elimination half‐life ranged from 8.7–10.1 hours. Renal dysfunction reduces levetiracetam clearance, and dosage reductions are recommended to prevent accumulation. Current CVVH dosing recommendations are based on predicted removal without clinical data. The volume of distribution and clearance in this case were similar to those of a normal healthy patient. Based on these results, we recommend considering an initial levetiracetam dose of 1000 mg every 12 hours for patients receiving CVVH, with dosage adjustments based on therapeutic drug monitoring.